2020
DOI: 10.3390/cancers12051309
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Serum Microbe-Derived Extracellular Vesicles and Diagnostic Models to Differentiate Ovarian Cancer and Benign Ovarian Tumor

Abstract: We aimed to develop a diagnostic model identifying ovarian cancer (OC) from benign ovarian tumors using metagenomic data from serum microbe-derived extracellular vesicles (EVs). We obtained serum samples from 166 patients with pathologically confirmed OC and 76 patients with benign ovarian tumors. For model construction and validation, samples were randomly divided into training and test sets in the ratio 2:1. Isolation of microbial EVs from serum samples of the patients and 16S rDNA amplicon sequencing were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Another field, where bacterial dysbiosis and metabolite signaling can be exploited, is therapy and diagnostics. There are numerous studies in the literature indicating that microbiome profiles in the intratumoral area (Wang et al 2020 ; Poore et al 2020 ), genital tract (Wang et al 2020 ; Zhou et al 2019a ), the serum (Kim et al 2020 ), or the peritoneum (Miao 2020 ) can be exploited as biomarkers to diagnose ovarian cancer. Metabolomics studies also revealed exploitable biomarkers (Turkoglu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another field, where bacterial dysbiosis and metabolite signaling can be exploited, is therapy and diagnostics. There are numerous studies in the literature indicating that microbiome profiles in the intratumoral area (Wang et al 2020 ; Poore et al 2020 ), genital tract (Wang et al 2020 ; Zhou et al 2019a ), the serum (Kim et al 2020 ), or the peritoneum (Miao 2020 ) can be exploited as biomarkers to diagnose ovarian cancer. Metabolomics studies also revealed exploitable biomarkers (Turkoglu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oncobiosis was identified in several compartments, including vaginal, cervicovaginal (Ness et al 2003 ; Nené et al 2019 ), upper genital tract (Zhou et al 2019a ; Brewster et al 2016 ), ovarian, intratumoral (Wang et al 2020 ; Banerjee et al 2017 ; Shanmughapriya et al 2012 ; Poore et al 2020 ), peritoneal (Miao et al 2020 ), serum (Kim et al 2020 ), and fecal (Mori et al 2019 ) compartments (Table 1 , Fig. 1 ).…”
Section: Oncobiotic Transformation In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent investigation regarding the use of extracellular vesicles-derived 16S for sequencing-based taxonomy identification was focused on the development of diagnostic models to differentiate ovarian cancer (OC) and benign ovarian tumor (BOT) [ 65 ]. In 2020, Kim and co-workers described the isolation of EVs from the serum of 166 patients with OC and 76 patients with BOT.…”
Section: Bacteria-derived Vesicles and 16s Rnamentioning
confidence: 99%
“…They can help evaluate microbiota composition [ 13 , 14 , 15 ]. A recent study, aimed to develop a diagnostic model for ovarian cancer, used microbiome profiles from serum bacteria-derived EVs alongside clinicopathologic data [ 16 ]. However, to the best of our knowledge, the association between the blood microbiome, assessed with bacteria-derived EVs, and PC has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%